On the practical use of papers: Users, land titles, land conflicts, and a history of archives in the Northern Andes of the Spanish empire (18th century) - Bohorquez, Jesús (2022)
In the eighteenth century, land titles played a central role in the resolution of land conflicts. This article addresses the different interactions that actors entertained with the production of papers (conservation, care, loss, recovery) not from a legal or theoretical perspective but from the perspective of its use, i.e., actors not as agents but as users. The use of papers refers to a non-theoretical or necessarily conscious handling of documents, and instead, emphasizes the practicalities of interacting with and transfering such papers to the archive. The issue is approached simultaneously from the perspective of both communal and private lands. Overall, works on the so-called «primordial titles» have taken as their main focus the pueblos de indios, and the management that indigenous authorities made of them. Scholars barely contrast the use that both communal and individual actors made of the papers they produced. This paper sheds light on this issue highlighting similarities and differences.